Monetary policy with judgment - Paolo Gelain; Simone Manganelli (European Central Bank (ECB), 2020)
Two approaches are considered to incorporate judgment in DSGE models. First, Bayesian estimation indirectly imposes judgment via priors on model parameters, which are then mapped into a judgmental interest rate decision. Standard priors are shown to be associated with highly unrealistic judgmental decisions. Second, judgmental interest rate decisions are directly provided by the decision maker, and incorporated into a formal statistical decision rule using frequentist procedures. When the observed interest rates are interpreted as judgmental decisions, they are found to be consistent with DSGE models for long stretches of time, but excessively tight in the 1980s and late 1990s and excessively loose in the late 1970s and early 2000s.
Keywords: E50; E58; E47; C12; C13; 330; Monetary Policy; DSGE; Maximum Likelihood; Statistical DecisionTheory